Regional Economic Outlook, September 2006, Asia and Pacific. (Regional Economic Outlook, 2006)
The September 2006 report analyzes recent developments, examines the impact of the recent market correction, and assesses potential for capital inflows and equity markets, as well as examining private consumption and trends in inequality. Chapters address financial developments in emerging Asia; the main macroeconomic issues facing policymakers; Asia's external surpluses; Asia's investment decline, and rebalancing growth in China.